Functional food science and substrate metabolism. - Saris, W; Asp, N; Björck, I; Blaak, E; Bornet, F; Brouns, F; Frayn, K; Fürst, P; Riccardi, G; Roberfroid, M; Vogel, M (1998)
The present review addresses the role of food constituents in the aetiology of metabolic conditions and chronic diseases, mostly related to energy metabolism and substrate regulation, such as obesity and non-insulin-dependent diabetes mellitus. Second, attention is paid to malnutrition, a major cause of mortality and morbidity in developing countries, which may be a cause of concern in Europe because of the increasing number of elderly people in the population. Finally, the role of diet during exercise, a condition of enormous substrate demands, is evaluated. Based on a critical evaluation of the existing knowledge in the literature, implications for future research in relation to functional foods are discussed.